Potential Misdiagnosis between COVID-19 and Dengue Infection Using Rapid Serological Test - Siti Qamariyah Khairunisa; Ilham Harlan Amarullah; Siti Churrotin; Anisa Lailatul Fitria; Mochammad Amin; Maria Inge Lusida; Soegeng Soegijanto (MDPI AG, 2021)
The coronavirus disease 2019 (COVID-19) pandemic that has a significant rapid transmission is an international public health concern. Several dengue-endemic countries reported similar clinical and laboratory features between COVID-19 and dengue in the early incubation period, and thus discerning the infection is difficult. As a dengue-endemic country, Indonesia also poses the same challenge during the COVID-19 outbreak. This current study analyzed the IgG and IgM profiles from COVID-19 patients by using a serological SARS-CoV-2 and dengue rapid test. In addition, 38 sera from healthy individuals (pre-COVID-19 date) were analyzed using a dengue rapid test. Among 120 samples, 4 samples indicated dengue IgG positive. However, IgM, NS1, and RT-PCR analyses showed negative results. Interestingly, regarding seropositivity of NS1 and DENV IgG from healthy individuals (pre COVID-19 infection), two samples were positive DENV IgG, while one of them was positive NS1. This suggested that in the dengue-endemic area, many people have already experienced dengue and have immunity against dengue virus. There is also the possibility of antibody cross-reactivity between COVID-19 and dengue infection. This also emphasizes the high demand for a rapid method with high sensitivity and specificity that can distinguish between SARS-CoV-2 and dengue.